Facilitator factors to develop a healthy ageing Social Prescribing local system in Portugal: A qualitative case study - Ribeiro, S.; Lopes, J. O.; Santos, O.; Capitão, C.; Martins, R.; Virgolino, A.; Alarcão, V.; Nogueira, P.; Henriques, A.; Seabra, P.; Arriaga, M.; Matos, C.; et al. (Journal of Infrastructure, Policy and Development, 2025)
Social Prescribing (SP) is an approach which aims of improving health and well-being and connecting patients to community services. Examples of these services include physical activity and cultural activities. Despite its benefits, SP has still not been fully implemented in Portugal. This case study is part of a larger study on Social Prescribing Local System (SPLS) implementation, which comprised a quantitative approach, a pilot study and a qualitative approach, and aims at exploring patients’ and healthcare workers’ perspectives on SP. The study was carried out to understand the motivations of different stakeholders for participating in the pilot project, the anticipated benefits for patients, healthcare professionals, and the health unit, as well as their perceptions and experiences within the scope of the SP project. Data collection was carried out in December 2020 through semi-structured individual interviews and a focus group. A total of seven participants were included, of which one patient, one museum representative and five healthcare professionals. Different common dimensions related to SP emerge, including health and well-being, social interaction and community engagement, accessibility and inclusivity, motivation and adherence, collaboration and coordination, and education and awareness. The patient considered the adequacy of the activity to the patient’s state of health and capabilities, adoption of a phased approach, with a focus on progress, in order to promote long-term adherence as facilitators. For the museum, disseminating its activities to healthcare professionals and patients through different channels such as posters at the health center, social media pages, and training sessions can significantly enhance visibility and engagement, while direct phone contact and digital publications can further promote adherence, ensuring a comprehensive and coordinated approach to patient participation and institutional benefit. Healthcare professionals identified several benefits, including reduction of social isolation and sedentarism, as well as a means of strengthening the therapeutic relationship with patients. The design and implementation of SP programs should be participative and involve all stakeholders participating in the process. Barriers to adherence included time for activity and the associated costs or prerequisites, availability of activities and lack of perceived interest in health.